1‐Methylcyclopropene suppressed the growth of Penicillium digitatum and inhibited the green mould in citrus fruit. Issue 2 (30th October 2020) - Wang, Zhiqiang; Yuan, Guofeng; Pu, Huili; Shan, Shuangshuang; Zhang, Zhengke; Song, Hongmiao; Xu, Xiangbin
Abstract: Postharvest green mould caused by Penicillium digitatum is one of the most important diseases in citrus fruit, which leads to fruit decay, green mould accumulation and huge economic losses. The inhibitory effect of 1‐methylcyclopropene (1‐MCP) on the postharvest green mould of citrus fruit was investigated. In vivo experiments showed that 1‐MCP significantly suppressed the green mould and the decay incidence in postharvest citrus fruit, and inhibited the mycelial growth and spore germination of P. digitatum . In vitro experiments, the lower integrity of plasma membrane, the higher content of reactive oxygen species (ROS) in spores and the higher content of malondialdehyde (MDA) in mycelium were detected in the 1‐MCP‐treated P. digitatum, showed that 1‐MCP increased oxidative damage and harmed the membrane integrity of P. digitatum . This study demonstrated that 1‐MCP inhibited postharvest green mould of citrus fruit by damaging the membrane integrity and influencing the growth of P. digitatum .